PENGEMBANGAN MODEL LOGIKA EVALUASI PROGRAM PENGEMBANGAN SDM RESPONSIF GENDER BIDANG ESDM - Rohmatulloh, R; Shalahuddin, Mohammad Imam (Jurnal Teknik Industri, 2014)
Logic model is a tool for telling the program in order to facilitate the evaluation. In a simple way, this model consists of the interrelation among the input-activity-output-outcome elements. This research aims to analyse the development of logic model for evaluating the human resources develoment in energy and mineral resources sectors related to the gender mainstreaming issue. It is developed through left-toright approach or forward logic. The result of study is the initial model based on the model development iteratively to achieve such outcomes the closest to the real conditions in gender-responsive human resources development. Expected program outcomes with increasing women?s participation in the following human resource development activities such as training, technical assistance, and the communication forum are increasing competence and role of women in the management of energy and mineral resources sector. This model can be used to evaluation process and enhanced in accordance with the needs and inputs from the stakeholders.